Childhood Obesity in a Rural Community: First Steps to Cultivating Change - Paige Turner Johnson; Michele Montgomery; Melissa Clark; Caitlin Taylor (Rural Nurse Organization; Binghamton University, 2017)
Purpose: This article describes how the Community Readiness Model was used to assess stage of readiness for childhood obesity prevention in a southern, rural county.  Sample:  Ten key informants were interviewed for the qualitative assessment of community readiness for change  and 100  county residents completed the attitudes for health promotion and disease prevention survey. Methods:  Using the Community Readiness Model as a guide, key informant interviews were conducted by the investigators in a rural county in the south located in the underserved area known as the Black Belt.  An interview template that examined community readiness for childhood obesity prevention was used by the investigators. Questions focused on attitudes towards children's physical activity and children's nutrition. In addition, questions regarding confidence in their community's ability to reduce childhood obesity, their schools and community's responsibility to address childhood obesity and who they thought might be interested in participating in a coalition to prevent childhood obesity were asked.  Results: The mean overall community readiness score for the 10 informants was 3.06, which corresponds with the vague awareness stage of readiness.  The lowest scores were for knowledge of the issue of childhood obesity, resources available, and community climate in regards to childhood obesity.  All of these scored in the denial/resistance stage of change.  Conclusions:  Before interventions can successfully be implemented within a community, community readiness for prevention programs and willingness to change must be assessed.  The overall CRM scores demonstrate that this county ranged from denial/resistance to vague awareness stages of change. These scores indicate that residents of this community may not be aware of the significance of childhood obesity in their community and efforts to move the community to a more active stage of change must be taken.  Keywords: Childhood obesity, Rural, Community readiness model, Obesity prevention, Community assessment, Rural health disparities DOI:  http://dx.doi.org/10.14574/ojrnhc.v17i2.456